L‐malic acid production from xylose by engineered Saccharomyces cerevisiae. Issue 3 (25th August 2021) - Kang, Nam Kyu; Lee, Jae Won; Ort, Donald R.; Jin, Yong‐Su
Abstract: L‐malic acid is widely used in the food, chemical, and pharmaceutical industries. Here, we report on production of malic acid from xylose, the second most abundant sugar in lignocellulosic hydrolysates, by engineered Saccharomyces cerevisiae . To enable malic acid production in a xylose‐assimilating S. cerevisiae, we overexpressed PYC1 and PYC2, coding for pyruvate carboxylases, a truncated MDH3 coding for malate dehydrogenase, and SpMAE1, coding for a Schizosaccharomyces pombe malate transporter. Additionally, both the ethanol and glycerol‐producing pathways were blocked to enhance malic acid production. The resulting strain produced malic acid from both glucose and xylose, but it produced much higher titers of malic acid from xylose than glucose. Interestingly, the engineered strain had higher malic acid yield from lower concentrations (10 g L ‒1 ) of xylose, with no ethanol production, than from higher xylose concentrations (20 and 40 g L ‒1 ). As such, a fed‐batch culture maintaining xylose concentrations at low levels was conducted and 61.2 g L ‒1 of malic acid was produced, with a productivity of 0.32 g L ‒1 h. These results represent successful engineering of S. cerevisiae for the production of malic acid from xylose, confirming that that xylose offers the efficient production of various biofuels and chemicals by engineered S. cerevisiae . Graphical Abstract and Lay Summary: L‐malic acid is widely used in the food, chemical, and pharmaceutical industries. In this study, the authors constructed the engineered Saccharomyces cerevisiae producing malic acid from xylose, the second most abundant sugar in lignocellulosic hydrolysates, and increased malic acid yield and productivity through the low‐level xylose fed‐batch strategy. This work suggests effective strategies in using xylose for the biological production of value‐added products.